Becoming vegetarian and vegan: rhetoric, ambivalence and repression in self-narrative - Carmichael,R (2002)
This thesis takes a discursive-rhetorical approach to becoming vegetarian and vegan. Previous studies have pointed to complexity and variety in definitions, types and most highly prized but ambivalently valued foodstuffs. The cultural and social criteria of vegetarianism, making `objective' studies difficult. Meat is also one of the meanings of diet in terms of `identities' are well established but the rhetorical approach taken here explores identity as accomplished through social practices offocus is on the complex and varied construction of social categories/identities in accounting. Rather than seeing variation and disagreement as problematic, analytic recast as dilemmas of identity and account-giving. accounts and the practices of justification and criticism. Cultural ambivalences areDiary and serial interview `case-material' was collected from 23 new and aspiringvegetarians and vegans. Participants' accounts are shown to handle a number of dilemmatic aspects of vegetarian/vegan identity; notably, a dilemma of moral superiority and a dilemma of abstinence. These dilemmas are discussed in terms of identity-management is argued to fundamentally involve relationships. Seen as stereotype-avoidance, commitment, and the co-construction of self and Other. Such biographical elements in self-construction, the inter-dependence of self- contexts, texts and resources for account-giving, relationships highlight both local and narratives/identities and the need for managing them, especially when identities are changed. A number of other rhetorical resources and practices used in the management of identity are also drawn out, including the discourses of lapsing, desire dilemmas of accounting through presenting the self as ambivalent, conflicted and and temptation and accounts of suppression and repression. The management of divided is underlined. Following recent work by Billig (e. g., 1999a), ambivalence and to a discussion of identity, contradiction and repression in terms o